Application of privacy, security and ethics in Islamic concerned ICT - Noordin, Mohamad Fauzan (IDOSI Publications, 2013)
Information and Communication Technology (ICT) plays an important role in development of the modern society which carries moral obligation to drive the society for an authenticated output. Ethical issues are directly related with ICT to diminish the unauthenticated uses of ICT applications. Ethics, rules, shariah and guidelines about the use of computers have been debated for years and many computer associations have existed from that; ACM, IEEE, Australian Computer Society, British Computer Society and others to assist the societies to restore and adapt the principles. Generally, all of these ethics that have been brought up by these societies are to preserve human rights, privacy and confidentiality which have been mentioned long ago in the Qur’an. Allah, the Most Merciful has cited in the Qur’an the shariah or standards for all human beings to live peacefully without harming others (security, privacy, authority, ethics) and perform ibadah as khalifah. The ACM for instance, has prepared the guidelines as ethical system for societies which cover moral imperatives and professional responsibilities for the computer professionals as the measurement of the code of conduct. Hence, from the revision and analytical reflection, it is examined and explored the moral value as well as the impact of Islam's prospect especially of the ethical issues by considering the Islamization a reality.